The effect of temperature on the duration of the effective pollination period in 'Oblica' olive (Olea europaea) cultivar. (3rd October 2013) - Vuletin Selak, G.; Cuevas, J.; Goreta Ban, S.; Pinillos, V.; Dumicic, G.; Perica, S.
Abstract The effective pollination period (EPP) was determined for 'Oblica' olive trees in response to sequential pollinations at anthesis and at increasing days after. The role played by each of three components of the EPP, namely the stigmatic receptivity, pollen tube growth and ovule longevity was examined and the duration of the EPP under different environmental conditions was calculated. An increase in temperature in the field was caused by enclosing bearing trees within polyethylene cages. The duration of the EPP varied between years and environmental conditions. Initial fruit set (IFS) declined gradually in response to sequential cross‐pollination. The significant decrease with respect to the maximum levels of IFS occurred 5 days after anthesis (DAA) in 2007 and between 4 and 5 DAA in 2010 at both environmental conditions. However, the fruit set decrease with sequential pollinations was sharper for the trees inside the cages than for trees growing at the open air, suggesting that high temperatures induce earlier and more pronounced decrease in flower fertility. The stigma receptivity was quite extended decreasing slowly with time. In 2010, the stigma receptivity was prolonged beyond sampling date (7 DAA) in both environmental conditions. Stigmas first lost the capacity to support pollen germination and later their capacity to adhere pollen grains. Pollen tube growth occurred rapidly and fertilization took place 1 or 2 days after pollination. Cross‐pollination resulted with higher fertilization levels, whereas fertilization was reduced and delayed under self‐pollination. Enclosing the trees within the cages had small effect on cross‐pollination but impaired the self‐pollination which resulted with reduced levels of fertilization. The ovule longevity was prolonged beyond the end of sampling in both years and conditions (beyond 9 DAA in 2009 or 7 DAA in 2010). Discrepancy between the estimates of the duration of the EPP based on analyses of its components and those indicated by the declines in fruit set from delayed pollination suggests that a different component of the pistil, the style, could have the critical role in determining the duration of the EPP.